(untitled) - Wood, L. S. (London, 1927)
This book introduce about England's heritage as a textile country. The obscure begings of the cotton industry in England. The dometic system, the great inventions, the improvement of communications...
Keywords: Ngành công nghiệp bông,Cotton textile industry